Mapping the Cross-Strait Studies as a Specific Research Field - Tonny Dian Effendi (Contemporary Chinese Political Economy and Strategic Relations: An International Journal)
Cross-strait relations encompass both political and security concerns and serve as a specialized research topic. Scholars approach the issue from various perspectives, and these analyses come not only from researchers in the core countries involved—China and Taiwan—and the United States (US), but also from experts worldwide. Research on cross-strait relations is rich in both analysis and prediction, extending beyond East Asia into broader international politics. What are the current research trends in cross-strait relations? Who studies them, and do scholars from certain countries bring unique topics or viewpoints? This study maps research on cross-strait relations using the Web of Science (WoS) database to identify and compare the dominant topics, scholars, and countries of affiliation. Through text, network, and sentiment analysis of bibliographic data, this study finds that cross-strait studies are not limited to the relations between Taiwan and China alone. Furthermore, the prevalence of Taiwanese scholars in this field suggests that much of the discourse reflects Taiwan’s perspective on cross-strait issues.